2020 5th International Conference on Smart and Sustainable Technologies (SpliTech) 2020
DOI: 10.23919/splitech49282.2020.9243697
|View full text |Cite
|
Sign up to set email alerts
|

An Affordable Vehicle-Mounted Sensing Solution for Mobile Air Quality Monitoring

Abstract: This paper presents the first prototype of the Expo-LIS system and its preliminary laboratory and field experiments. The ExpoLIS system is composed of an affordable vehiclemounted mobile sensor network and its supporting user-centred services whose aim is to provide citizens with real-time and dense spatiotemporal air quality data. A set of preliminary static laboratory experiments and dynamic field experiments were conducted, showing that the current prototype is already able to track changes in the air quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Other studies have investigated low-cost sensor performance when mounted to vehicles, but not with mobile reference or higher-grade monitors for comparison, and with differing levels of sophistication. 18,61,64,65 In this study, we tested low-cost sensor nodes containing optical PM sensors and electrochemical sensors sampling from a car while mobile, against reference and "mid-cost" instruments, also mounted to the car. Three sensor nodes were housed in a roof box on top of the car.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Other studies have investigated low-cost sensor performance when mounted to vehicles, but not with mobile reference or higher-grade monitors for comparison, and with differing levels of sophistication. 18,61,64,65 In this study, we tested low-cost sensor nodes containing optical PM sensors and electrochemical sensors sampling from a car while mobile, against reference and "mid-cost" instruments, also mounted to the car. Three sensor nodes were housed in a roof box on top of the car.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As an illustration, Santana et al. (2020) developed a cost‐effective sensing solution that can be mounted on vehicles to monitor air quality in motion. Similarly, Alessandroni et al.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a notable increase in the utilization of vehicles as mobile sensor carriers in various literature and advanced platforms. As an illustration, Santana et al (2020) developed a costeffective sensing solution that can be mounted on vehicles to monitor air quality in motion. Similarly, Alessandroni et al (2015) employed mobile devices affixed to the car cabin to detect road roughness.…”
mentioning
confidence: 99%
“…The research reported here is part of the ExpoLIS project. Our goal in the ExpoLIS project is to deploy a network of mobile LCS to monitor air quality and to develop a set of software tools [28]. This paper is an extended version of our previous work [18] aiming at developing a pollution prediction software tool to assist the population.…”
Section: Introductionmentioning
confidence: 99%